1992
DOI: 10.1111/j.1365-2044.1992.tb02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural infusion for postoperative pain relief following abdominal aortic surgery: bupivacaine, fentanyl or a mixture of both?

Abstract: SummaryThirty patients who had undergone elective abdominal aortic surgery were studied in a prospective, randomised double-blind comparison of thoracic epidural 0.2% bupivacaine alone, thoracic epidural fentanyl alone and thoracic epidural 0.2% bupivacaine combined with ,fentanyl. Pain relief, pulmonary function. cardiovascular stability and side effects were assessed. Pain relief was e.ucellent in the combined bupivacaine-fentanyl series, being signiJicantly better than the other groups ( p < 0.05) during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 34 publications
5
28
0
1
Order By: Relevance
“…This may be why more patients had pain (VAPS score > 2) during the first 2 postoperative hours than after 4 h. It may also account for the relatively low mean fentanyl and sufentanil requirement compared with other studies. The mean administered dose, 27.5/~g/h fentanyl, was less than in comparable studies in which 46-60 /~g/h fentanyl was administered [12][13][14]. The distribution of the patients over the VAPS 8 classes is in accordance with the results of George et al [14].…”
Section: Postoperative Studysupporting
confidence: 81%
“…This may be why more patients had pain (VAPS score > 2) during the first 2 postoperative hours than after 4 h. It may also account for the relatively low mean fentanyl and sufentanil requirement compared with other studies. The mean administered dose, 27.5/~g/h fentanyl, was less than in comparable studies in which 46-60 /~g/h fentanyl was administered [12][13][14]. The distribution of the patients over the VAPS 8 classes is in accordance with the results of George et al [14].…”
Section: Postoperative Studysupporting
confidence: 81%
“…From these data we calculated approximately equipotent 24-h dosages for each drug. Previous studies have demonstrated superior analgesia with a combination of opioid and bupivacaine with the possible exception of very high dose fentanyl and therefore the use of bupivacaine alone or opioid alone were not considered ethical [10,[24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…It is common practice to infuse a mixture of bupivacaine 0.1-0.25% with an opioid for postoperative analgesia [11][12][13][14]. A relatively low concentration of bupivacaine (0.0625%) plus fentanyl 3.3 mg.ml ¹1 has been chosen as our standard analgesic protocol and most of these patients are monitored in the general ward.…”
Section: Discussionmentioning
confidence: 99%